UMP, IMPACT MALAYSIA seal collaboration of Youth and Community Innovation programme - Mimi Rabita, Abd Wahit (UMPSA, 2022)
KUALA LUMPUR, 1 September 2022 - Universiti Malaysia Pahang (UMP) and IMPACT MALAYSIA are working together on technology, community and business impact that enables collaborative interaction between various stakeholders through all programmes to be implemented.